PORNOGRAFI DAN PORNOAKSI DALAM PERSPEKTIF HUKUM ISLAM (Studi atas Signifikansi Pemikiran Muhammad Syahrur) - Nur, Agus Waluyo (Al-Mawarid Jurnal Hukum Islam, 2006)
The pornography and pornoaction phenomena that happen in Indonesia make society resentment. They try to solve the problem wisely. Many efforts are conducted to minimize, instead, to reject their the negative effect. Recently, the proposed manuscript act concerning pornography and pornoaction. The aims of the act is becoming reference and guidance for Indonesian people. The writer of the following article tries to relate Shahrur?s theory of Islamic Law. According to the writer, Shahrurâs methodology of Islamic Law should be considered for solving the problem of pornography and pornoaction in Indonesia. Kata kunci: Syahrur, hukum Islam, pornografi, dan pornoaksi.